Effect of Plastic Synthetic Aggregate in the Production of Lightweight Concrete - MBADIKE, ELIVS M.; G.C., EZEOKPUBE (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
In this research work, the effect of plastic synthetic aggregate in the production of lightweight concrete was studied. The plastic synthetic aggregate was used to replace 0-40% of coarse aggregates. A mix proportion of 1:1.8:3.7 with water cement ratio of 0.47 were used. Concrete cubes of 150mmx150mmx150mm of coarse aggregate/plastic synthetic aggregate were cast and cured at 3,7,28,60 and 90 days respectively. At the end of each hydration period, the three concrete cubes for each hydration period were crushed and their average compressive strength recorded. A total of ninety (90) concrete cubes were cast. The result of the compressive strength tests for 5-40% replacement of coarse aggregates with plastic synthetic aggregate ranges from 8.07-36.71N/mm2 as against 24.58-41.21N/mm2 for the control test. The workability for 5-40% replacement of coarse aggregates with plastic synthetic aggregate ranges from 12-61mm as against 8mm for the control test (0% replacement).